If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 20 = 2y + 7 Reorder the terms: 20 + 3x = 2y + 7 Reorder the terms: 20 + 3x = 7 + 2y Solving 20 + 3x = 7 + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 3x = 7 + -20 + 2y Combine like terms: 20 + -20 = 0 0 + 3x = 7 + -20 + 2y 3x = 7 + -20 + 2y Combine like terms: 7 + -20 = -13 3x = -13 + 2y Divide each side by '3'. x = -4.333333333 + 0.6666666667y Simplifying x = -4.333333333 + 0.6666666667y
| 20m-25m^2= | | 13.6=20-x | | 79+5d=169 | | 15=2m-19 | | 3+5m=2m+(-9) | | 5+5m=2m+(-9) | | x-(-3.9)=5.9 | | 8=x+9+98 | | 6+11x=-24+x | | -2x+2=x+5 | | 689=65+104x | | 2x+2=2x+5 | | Kxsquared-6x+2=0 | | -2+2x=8+23x | | -16t^2+215t-97=0 | | 58-4x=8-9x | | 285=3x-75 | | 7Y-3=37-3Y | | 3+6x=-27+x | | 2(31+4)=I-7 | | cosA=0.8 | | 3w^2+21w=0 | | P-14=7P+28 | | 2(m+2)=11 | | 4w^2+20w=0 | | 10(7)+100x=30(7+x) | | 4H+15=8-3H | | 10x-7=6x-21 | | 11n-3=9n+5 | | 10x-7=6x-12 | | -(9x-3)-(5x-5)+7=-9(x-1)-(9x+9)+3 | | 12+5L=30-4L |